The Correlation Analysis between Korean Middle School Students’ Emotional Level and Friendship in Science Learning - Kim, D. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study aimed to find out the correlation between emotional levels and friendship in science learning. The participants in this study were 30 third-grade students at a girls’ middle school in a Korean metropolitan city. For nine months, their science classes were conducted by one teacher in charge of science class and five students were organized into a group. The science learning emotional test tool consisted of 35 questions on the rating scale of 5 phases and the peer nomination method was adopted for the friendship survey in science learning. The test was conducted during the last hour of science class. In the results of analyzing students’ science learning emotion levels, students showed high average scores in three emotional elements of positive science learning (joy, satisfaction, and interest), showing overall positive feelings about science learning. After analyzing friendship among the students, the connection between students was analyzed to be close to 1 and none of the students were isolated. Two out of 30 students were given ninth appointment from peers and formed a central axis in the classroom network. On the other hand, two students in the class were not chosen by other students and only pointed out helpful colleagues in science learning. After analyzing the correlation between the emotional level and friendship in science learning based on these two studies, it was analyzed that there was a strong static correlation between two variables. Therefore, since the bond between emotion and friendship in science learning is closely related, there is a need for science learning to take into account the interrelationship between two variables.